2022
DOI: 10.1093/iob/obac034
|View full text |Cite
|
Sign up to set email alerts
|

Precocious Sperm Exchange in the Simultaneously Hermaphroditic Nudibranch,Berghia stephanieae

Abstract: Sexual systems vary greatly across molluscs. This diversity includes simultaneous hermaphroditism, with both sexes functional at the same time. Most nudibranch molluscs are thought to be simultaneous hermaphrodites, but detailed studies of reproductive development and timing remain rare as most species cannot be cultured in the lab. The aeolid nudibranch, Berghia stephanieae, is one such species that can be cultured through multiple generations on the benchtop. We studied B. stephanieae reproductive timing to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…In the present study, sub-adults were communally housed and although they had not laid eggs yet and had no eggs visible in their reproductive organs when they were sacrificed, these animals likely had already mated. Precocious mating with early sperm donation, weeks prior to egg-laying, was recently reported in B. stephanieae (Taraporevala et al, 2022). We found that in sub-adults capable of this behavior (N=5), all 18 neuron classes seen in adults were identifiable (Figure 6A).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…In the present study, sub-adults were communally housed and although they had not laid eggs yet and had no eggs visible in their reproductive organs when they were sacrificed, these animals likely had already mated. Precocious mating with early sperm donation, weeks prior to egg-laying, was recently reported in B. stephanieae (Taraporevala et al, 2022). We found that in sub-adults capable of this behavior (N=5), all 18 neuron classes seen in adults were identifiable (Figure 6A).…”
Section: Resultsmentioning
confidence: 90%
“…This is reminiscent of what was observed in L. stagnalis ; transcription of ELH in young animals builds until it is released by translation which happens at the time of egg-laying (De Lange et al, 1994). Behavioral work in B. stephanieae recently showed that even virgin B. stephanieae that were isolated their entire lives eventually laid eggs, albeit weeks later than animals in their cohort that had access to mates (Taraporevala et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…We cultured Berghia stephanieae juveniles using the same methods as prior B. stephanieae imaging work [35, 36]. We starved juveniles for five days prior to fixation to decrease autofluorescence from digestive contents.…”
Section: Methodsmentioning
confidence: 99%
“…Berghia stephanieae (hereafter referred to as Berghia ) is a species of gastropod in the order Nudibranchia, a clade of marine slugs that lose their shell during metamorphosis [33]. This species has been used as a model for the study of both more conserved systems, such as neurodevelopment [34] and reproductive development [35], as well as clade-restricted phenotypes such as the sequestration of cnidarian nematocysts [36, 37] and endosymbiosis [38, 39]. We combined an inferred proteome from Berghia with available genome and transcriptome data from other metazoan species – including mollusks such as cephalopods, bivalves, and other gastropods – to identify clade-specific Berghia genes (i.e., restricted to Mollusca, Gastropoda, Heterobranchia, Nudibranchia, Aeolidina, or Berghia alone).…”
Section: Introductionmentioning
confidence: 99%
“…Berghia stephanieae (hereafter referred to as Berghia ) is a species of gastropod in the order Nudibranchia, a clade of marine slugs that lose their shell during metamorphosis [ 33 ]. This species has been used as a model for the study of both more conserved systems, such as neurodevelopment [ 34 ] and reproductive development [ 35 ], as well as clade-restricted phenotypes such as the sequestration of cnidarian nematocysts [ 36 , 37 ] and endosymbiosis [ 38 , 39 ]. We combined an inferred proteome from Berghia with available genome and transcriptome data from other metazoan species—including mollusks such as cephalopods, bivalves, and other gastropods—to identify clade-specific Berghia genes (i.e., restricted to Mollusca, Gastropoda, Heterobranchia, Nudibranchia, Aeolidina, or Berghia alone) (Fig.…”
Section: Introductionmentioning
confidence: 99%